Taphonomy, palaeoecology and palaeobiological significance of the Cisterna quarry fossil site: An exceptional window into the marine vertebrate biodiversity of the early Late Miocene Mediterranean Sea - Giovanni Bianucci; Giulia Bosio; Giorgio Carnevale; Antonio Cascella; Francesco Nobile; Emanuele Peri; Alberto Collareta (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Quantitative analysis of Upper Miocene Mediterranean reef carbonates: A tool for reconstructing palaeoenvironmental gradients - Giovanni Coletti; Alberto Vimercati; Francesca R. Bosellini; Luca Mariani; Adriano Guido; Alessandro Vescogni; Jesús Reolid; Gerald Auer; Daniela Basso; Alberto Collareta; Giulia Bosio; Or Mordecai Bialik (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The earliest dinosaur-dominated fauna? A reappraisal of the Carnian Lerici tracksite and the first global radiation of Sauropodomorpha - Lorenzo Marchetti; Alberto Collareta; Valerio Granata; Matteo Belvedere (Gondwana Research, 2026)

New whale barnacle records from eastern North America (Early Pleistocene of the Carolinas, USA, and Late Pleistocene or Early Holocene of Montreal, Canada) - Andy Gale; Alberto Collareta (Proceedings of the Geologists' Association, 2026)

The earliest Neogene vertebrate assemblage of the Pisco Basin, Peru - Giuseppe Marramà; Alberto Collareta; Giulia Bosio; Giovanni Bianucci; Elisa Malinverno; Claudio Di Celma; Francesco Nobile; Luca Pellegrino; Alí Altamirano-Sierra; Mario Urbina; Igor M. Villa; Jaime A. Villafaña; et al. (Journal of South American Earth Sciences, 2026)

Fossil sardines from the Pisco Formation (Miocene), Peru: Taxonomy, taphonomy, and paleoecology - Giorgio Carnevale; Luca Pellegrino; Giulia Bosio; Giovanni Bianucci; Alberto Collareta; Claudio Di Celma; Elisa Malinverno; Abel Alejandro Ramirez Ampuero; Luz Tejada-Medina; César Chacaltana; Mario Urbina; Giuseppe Marramà (Palaeoworld, 2026)

A window into a middle Eocene mesotrophic mixed siliciclastic-carbonate system from the South American Pacific margin (Paracas Formation, Pisco Basin, Peru) - Giovanni Coletti; Luca Mariani; Elisa Malinverno; Alberto Vimercati; Claudio Di Celma; Alberto Collareta; Giancarlo Molli; Giovanni Sarti; Giovanni Bianucci; Orangel Aguilera; Alessandro Cavallo; Mario Urbina; et al. (Journal of South American Earth Sciences, 2026)

Bioapatite crystallinity and Rare Earth Element signatures in fossil and Recent sharks: A window into Past and Present seas - Luca Medici; Annalisa Ferretti; Alberto Collareta; Giulia Bosio; Giovanni Bianucci; Giorgio Carnevale; Simone Casati; Simona Clò; Luca Lanteri; Federico Lugli; Giuseppe Marramà; Frederik H. Mollen; et al. (Chemical Geology, 2026)

Calcium Isotopes Correlate With Baleen Whale Feeding Ecology - Jeremy E. Martin; William M. G. Parker; Olivier Lambert; Giovanni Bianucci; Alberto Collareta; Romain Amiot; Arnauld Vinçon‐Laugier; Felix G. Marx (Marine Mammal Science, 2026)
Baleen whales are among the largest animals ever and engineer marine ecosystems by transporting nutrients both vertically through the water column and across vast oceanic distances. Hidden underwater, their feeding habits often remain unseen and hence must be studied indirectly based on stomach contents and stable isotopes. Here, we explore the potential of bone‐bound calcium isotopes as a chemical proxy for extant baleen whale foraging ecology. Unlike bulk nitrogen and various trace elements (Mg, Sr, and Ba), calcium isotopes clearly distinguish gulp ( n = 4 species) from skim feeders ( n = 4 species) and provide a powerful tool to infer diet and feeding strategies. The difference in calcium isotope composition plausibly reflects incidental ingestion of seawater, which may be more pronounced in skim feeding whales than previously thought.

Retrieving Palaeoecological Information from Historic Fossil Finds: A Taphonomic Cold Case from Orciano Pisano (Central Italy) Reveals a Distinctive Trophic Interaction in the Pliocene Mediterranean Sea - Edoardo Terranova; Giovanni Bianucci; Marco Merella; Chiara Sorbini; Alberto Collareta (Journal of Marine Science and Engineering, 2025)
Evidence of trophic interactions between sharks and cetaceans is rather widespread in the fossil record, consisting as it does of tooth marks on bones and rarer teeth or tooth fragments embedded in (or associated with) skeletal remains. Here, we reappraise a partial mysticete (baleen whale) forelimb that was collected more than a century ago from Pliocene deposits exposed at the celebrated fossil locality of Orciano Pisano (Tuscany, central Italy). This specimen, which is revealed to originate from an early juvenile individual, features shark tooth marks on both the humerus and radius. Whether these traces are due to active predation or to scavenging cannot be ascertained. During the Pliocene, the Mediterranean Basin was inhabited by a diverse elasmobranch fauna, including a number of mammal-eating forms that no longer inhabit the Mediterranean Sea (e.g., Galeocerdo and some Carcharhinus spp. as well as the extinct Parotodus). Early juvenile mysticetes were also likely more common than today in the Pliocene Mediterranean Sea, which may have contained balaenid and balaenopterid calving grounds, thus providing the Mediterranean mammal-eating sharks with vulnerable, energetically valuable potential prey items. Thus, our results evoke a kind of trophic interaction that was likely common and ecologically relevant in the Pliocene Mediterranean Sea.

New early Pliocene Rhinocerotidae findings from Tuscany (Italy) and the Pliocene rhinocerotine record in Italy - Luca Pandolfi; Alberto Collareta; Dariusz Nowakowski; Giovanni Bianucci; Lorenzo Rook (Geobios, 2025)

Unraveling marine phosphogenesis along the Miocene coast of Peru: Origin and sedimentological significance of the Pisco Formation phosphorites - Giulia Bosio; Anna Gioncada; Elisa Malinverno; Giovanni Coletti; Alberto Collareta; Luca Mariani; Alessandro Cavallo; Giovanni Bianucci; Mario Urbina; Claudio Di Celma (Marine and Petroleum Geology, 2024)

Double-phased controlled and influenced biomineralization in marine invertebrates: The example of Miocene to recent reef-building polychaete cirratulids from southern Peru - Adriano Guido; Francesco D'Amico; Thomas J. DeVries; Tomáš Kočí; Alberto Collareta; Giulia Bosio; Rossana Sanfilippo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Barnacle-rich facies as a tool for palaeoenvironmental reconstructions - Giovanni Coletti; Giulia Bosio; Alberto Collareta; Or Mordecai Bialik; Eleonora Regattieri; Irene Cornacchia; Gianni Insacco; John Buckeridge (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Taphonomy of a Mysticete Whale from the Lower Pliocene of the Coast of Cádiz (Spain) - Giulia Bosio; Ildefonso Bajo-Campos; Alberto Collareta; Sergio Ros-Montoya; Daniel de la Torre; Giovanni Coletti; Giovanni Bianucci (Journal of Marine Science and Engineering, 2023)
A fossil mysticete was discovered along the southwestern coast of Spain, occurring in a block detached from the Neogene deposits exposed along a coastal cliff at the locality of Conil de la Frontera (Cádiz, Spain). These deposits range from Pliocene to Pleistocene in age and include shallow-marine, mixed carbonate–siliciclastic sediments, with the whale being found in occurrence of a stratigraphic unconformity marked by Thalassinoides burrows. 87Sr/86Sr analyses on oyster shells associated with the skeleton suggest an Early Pliocene age, in agreement with the age of the lowermost unit cropping out at the study site. The studied cetacean specimen consists of an articulated, almost complete balaenopteroid skeleton exposed in the field dorsal side up; being contained in an upside-down block, however, it is preserved in ventral disposition. Bones exhibit a low degree of preservation of the cortical bone tissue, which locally features shark bite marks and Osedax traces as well as abundant encrustations of barnacles and ostreids. Two shark teeth were also found near the skeleton. Bones have preserved their main histological features, even though they locally exhibit microcracks, dissolution, substitution by Fe oxides, and microborings. Sediment particles and late diagenetic cements fill the medullary cavities. We propose that the whale carcass experienced refloating before sinking to the seafloor and that the skeleton was probably exposed on the seafloor for some time before being eventually buried.

The Palaeobiology of the False Mako Shark, Parotodus benedenii (Le Hon, 1871): A View from the Pliocene Mediterranean Sea - Alberto Collareta; Simone Casati; Andrea Di Cencio (Journal of Marine Science and Engineering, 2023)
The extinct “false mako” shark, Parotodus benedenii (Lamniformes: Otodontidae), is essentially known from large, robust teeth that are widespread but overall rare in Oligocene to Pliocene deposits worldwide. More than 150 years after its description, this species still represents a palaeontological conundrum, as very little is known about its body aspect and palaeoecology. Here, we describe new specimens of P. benedenii from the Pliocene of Tuscany, central Italy. These new finds comprise some of the geologically youngest finds of P. benedenii worldwide, witnessing to the survival of false makos until the Late Pliocene at least, which in turn suggests that P. benedenii may have been the latest surviving member of the family Otodontidae. Building upon a thorough literature review, we provide an updated synthesis of the palaeobiology of P. benedenii. In light of the morphological evidence, and considering previously published suggestions, P. benedenii may be reconstructed as a large-sized, carnivorous shark that dwelt in pelagic settings and fed primarily on large, soft prey and scavenging items. Thus, some ecological partitioning did likely exist between P. benedenii and other elasmobranch apex predators of the Neogene mid-latitude seas (including, in Pliocene times, the extant species Carcharodon carcharias, Carcharhinus leucas and Galeocerdo cuvier).

Pliocene Geotourism: Innovative Projects for Valorizing the Paleontological Heritage of Three Different-Staged Quarries of Tuscany (Central Italy) - Marco Merella; Alberto Collareta; Simone Casati; Andrea Di Cencio; Giovanni Bianucci (Geoheritage, 2023)
Quarries are areas of pivotal importance for investigation, popularization, and educational purposes in the field of geosciences. Here, we focus on three quarries of Tuscany (La Serra, Arcille, and Certaldo) that have been home to significant finds of marine vertebrate fossils. The three selected localities are representative of the many active (La Serra), inactive (Arcille), and abandoned (Certaldo) Tuscan quarries where vertebrate-bearing Pliocene deposits are exposed. Given the richness and scientific value of their paleontological content (including holotypes as well as otherwise unique specimens), the abundance of exposed sedimentary structures, and the high potential for open-air musealization, the La Serra, Arcille, and Certaldo quarries should be regarded as geosites. These quarries are thoroughly described, and several suggestions for their preservation and valorization are proposed, focusing on their importance for geotourism, with the goal of reaching out to the broadest audience possible. Many innovative dissemination tools, including 3D technologies, are now available for pursuing such an aim.

Turtle barnacles have been turtle riders for more than 30 million years - Alberto Collareta; Michael W. Rasser; Eberhard Frey; Mathias Harzhauser (PalZ, 2023)
In contrast to other kinds of biological interactions, symbiosis is a scarcely investigated aspect of the fossil record. This is largely due to taphonomic biases that often frustrate any attempt to make a strong case that two organisms shared an intimate association in life. Among extant marine vertebrates, the sea turtles (Cheloniidae and Dermochelyidae) bear a broad and diverse spectrum of epibiotic symbionts, including specialists such as the turtle barnacles (Chelonibiidae and Platyleapadidae). Here, we reappraise an early Oligocene (Rupelian) fossil cheloniid skeleton, featuring the remains of cirripedes on the exterior of its entoplastron, from the Rauenberg fossil-lagerstätte , southwestern Germany. The barnacle specimens are assigned to Protochelonibia melleni , an extinct protochelonibiine species and the geologically oldest known member of Chelonibiidae. In the light of taphonomic and palaeoenvironmental considerations, and given that the extant chelonibiids are mostly known as epizoic symbionts of sea turtles, we conclude that this unique fossil association resulted from the epizoic growth of the barnacles on the external surface of the plastron of the turtle during its lifetime. This remarkable fossil association provides evidence that chelonibiids, including the extinct protochelonibiines, have been chelonophilic epizoans for more than 30 Myr. A survey of the trace and body fossil records shows that platylepadids are also likely as old as the Rupelian as is their symbiotic association with cheloniid hosts. This early emergence of the modern-looking, turtle-dwelling barnacle lineages corresponds to a climate-driven phase of major radiation and taxonomic turnover among sea turtles at the Eocene–Oligocene transition.

Symbiont-Bearing Colonial Corals and Gastropods: An Odd Couple of the Shallow Seas - Giovanni Coletti; Alberto Collareta; Andrea Di Cencio; Giulia Bosio; Simone Casati (Journal of Marine Science and Engineering, 2023)
In order to investigate the serendipitous find of a gastropod encrusted by the symbiont-bearing colonial coral Oculina patagonica, we examined several specimens of cnidarian-encrusted gastropods, ranging in age from the Pliocene to the Recent, and characterized in detail their sclerobiont cover. The results of our analysis suggest that gastropod shells can be encrusted by symbiont-bearing colonial corals at various times: (1) when the gastropod is alive; (2) when the shell is being used by a secondary inhabitant (e.g., hermit crabs or sipunculid worms); (3) when the shell is discarded but yet to be buried. The relationship between the symbiont-bearing coral and the inhabitant(s) of the encrusted shell is an example of facultative mutualism, i.e., it is non-obligate yet beneficial for both ends as the former obtains the capability to move, and the latter improves the resistance and resilience of its armor, thus obtaining extra protection from predators. Being able to move could prove particularly useful for a symbiont-bearing coral because, in addition to removing the risk of being smothered by sediment, it would also favor the photosynthetic activity of its algal endosymbionts by allowing the coral to be always clean of sedimentary particles. Although the resulting epibiotic association would be limited in size by the ability of either the gastropod or the secondary inhabitant of the shell to move at the seafloor, these small and easy-to-miss benthic islands might become the seeds that allow sessile carbonate producers such as hermatypic colonial corals to colonize unconsolidated substrates.

Ghosts of the Holobiont: Borings on a Miocene Turtle Carapace from the Pisco Formation (Peru) as Witnesses of Ancient Symbiosis - Alberto Collareta; Rafael Varas-Malca; Giulia Bosio; Mario Urbina; Giovanni Coletti (Journal of Marine Science and Engineering, 2022)
In spite of the widespread occurrence of epibiotic turtle barnacles (Coronuloidea: Chelonibiidae and Platylepadidae) on extant marine turtles (Chelonioidea: Cheloniidae and Dermochelyidae), and although the association between these cirripedes and their chelonian hosts has existed for more than 30 million years, only a few studies have investigated the deep past of this iconic symbiotic relationship on palaeontological grounds. We describe probable platylepadid attachment scars in the form of hemispherical/hemiellipsoidal borings on an Upper Miocene (Tortonian) fragmentary turtle carapace, identified herein as belonging to Cheloniidae, from the Pisco Lagerstätte (East Pisco Basin, southern Peru). When coupled with the available molecular data, this and other similar ichnofossils allow for hypothesising that platylepadid symbionts were hosted by sea turtles as early as in early Oligocene times and became relatively widespread during the subsequent Miocene epoch. Chelonian fossils that preserve evidence of colonisation by platylepadid epibionts in the form of pits on the turtle shell should be regarded as fossil holobionts, i.e., palaeontological witnesses of discrete communal ecological units formed by a basibiont and the associated symbionts (including the epibiota). A greater attention to the bone modifications that may be detected on fossil turtle bones is expected to contribute significantly to the emerging field of palaeosymbiology.

Dental Morphology, Palaeoecology and Palaeobiogeographic Significance of a New Species of Requiem Shark (Genus Carcharhinus) from the Lower Miocene of Peru (East Pisco Basin, Chilcatay Formation) - Alberto Collareta; René Kindlimann; Alessio Baglioni; Walter Landini; Giovanni Sarti; Alí Altamirano; Mario Urbina; Giovanni Bianucci (Journal of Marine Science and Engineering, 2022)
Nowadays, the requiem sharks comprise one of the most diverse and widespread families of selachians, i.e., Carcharhinidae. Among the carcharhinids, the genus Carcharhinus has the largest number of living species, namely, at least 35. Known from fossils as old as the Cretaceous, the requiem sharks did not significantly radiate before the Eocene (when Carcharhinus also appeared), and their diversification mainly occurred in Neogene times. Here, we describe a new species of requiem shark, Carcharhinus dicelmai sp. nov., based on fossil teeth from Lower Miocene (18.4–18.1 Ma) strata of the Chilcatay Formation of the East Pisco Basin (southern Peru). Upper teeth of C. dicelmai sp. nov. are typically provided with a slender, smooth-edged cusp; a marked coronal twist; and a distal heel that bears 1–5 coarse, angularly lobate serrae that become more prominent toward the base of the cusp. The dentition of C. dicelmai sp. nov. appears less akin to that of most other carcharhines to the cutting-clutching type, and seemingly testifies to the development of more predominantly clutching adaptations. A carcharhinid tooth from the Burdigalian to lower Langhian Cantaure Formation of Venezuela is reassigned to C. dicelmai sp. nov., suggesting a trans-Panamanian distribution for this extinct shark species.

New and overlooked occurrences of the rarely reported protochelonibiine “turtle” barnacles from the Oligocene and Miocene of Europe - Alberto Collareta; Mathias Harzhauser; Michael W. Rasser (PalZ, 2022)

Vertebrate Palaeoecology of the Pisco Formation (Miocene, Peru): Glimpses into the Ancient Humboldt Current Ecosystem - Alberto Collareta; Olivier Lambert; Felix G. Marx; Christian de Muizon; Rafael Varas-Malca; Walter Landini; Giulia Bosio; Elisa Malinverno; Karen Gariboldi; Anna Gioncada; Mario Urbina; Giovanni Bianucci (Journal of Marine Science and Engineering, 2021)
The northward-flowing Humboldt Current hosts perpetually high levels of productivity along the western coast of South America. Here, we aim to elucidate the deep-time history of this globally important ecosystem based on a detailed palaeoecological analysis of the exceptionally preserved middle–upper Miocene vertebrate assemblages of the Pisco Formation of the East Pisco Basin, southern Peru. We summarise observations on hundreds of fossil whales, dolphins, seals, seabirds, turtles, crocodiles, sharks, rays, and bony fishes to reconstruct ecological relationships in the wake of the Middle Miocene Climatic Optimum, and the marked cooling that followed it. The lowermost, middle Miocene Pisco sequence (P0) and its vertebrate assemblage testify to a warm, semi-enclosed, near-shore palaeoenvironment. During the first part of the Tortonian (P1), high productivity within a prominent upwelling system supported a diverse assemblage of mesopredators, at least some of which permanently resided in the Pisco embayment and used it as a nursery or breeding/calving area. Younger portions of the Pisco Formation (P2) reveal a more open setting, with wide-ranging species like rorquals increasingly dominating the vertebrate assemblage, but also local differences reflecting distance from the coast. Like today, these ancient precursors of the modern Humboldt Current Ecosystem were based on sardines, but notably differed from their present-day equivalent in being dominated by extremely large-bodied apex predators like Livyatan melvillei and Carcharocles megalodon.

Remarkable multicuspid teeth in a new elusive skate (Chondrichthyes, Rajiformes) from the Mediterranean Pliocene - Alberto Collareta; Frederik H. Mollen; Marco Merella; Simone Casati; Andrea Di Cencio (PalZ, 2021)
Here we report on four highly peculiar skate teeth from Arcille and Certaldo, two Pliocene localities of Tuscany (central Italy). While being attributable to Rajiformes and somewhat reminiscent of Dipturus and Rostroraja , these specimens display an unusual multicuspid tooth design that does not match any extinct or extant skate taxon known to date. The studied teeth are thus referred to a new genus and species of Rajiformes, Nebriimimus wardi gen. et sp. nov., which is here tentatively assigned to the family Rajidae. Based on pronounced morphological similarities between the rather large-sized teeth of the latter and those of extant nurse sharks, we hypothesise that N. wardi might have been capable of actively foraging upon relatively large food items compared to other rays. This extinct skate species was likely not a common component of the Pliocene Tuscan marine vertebrate assemblages. The palaeoenvironmental scenarios that N. wardi inhabited were marginal-marine and open shelf settings characterised by tropical climate conditions. As N. wardi is currently known only from lower to mid-Pliocene deposits of the Mediterranean Basin, it is tempting to speculate that its speciation dates back to an earliest Pliocene phase of diversification that also contributed to the emergence of the Mediterranean endemic stock of extant skate species.

Piscivory in a Miocene Cetotheriidae of Peru: first record of fossilized stomach content for an extinct baleen-bearing whale - Alberto Collareta; Walter Landini; Olivier Lambert; Klaas Post; Chiara Tinelli; Claudio Di Celma; Daniele Panetta; Maria Tripodi; Piero A. Salvadori; Davide Caramella; Damiano Marchi; Mario Urbina; et al. (The Science of Nature, 2015)